Models of digitisation of organisational space in sport - Wojciech Cieśliński; Paweł Piepiora; Kazimierz Witkowski (Kazimierz Wielki University, 2019)
This research presents the organisational model of digitisation of sport institutions as the element of development shifting towards digital models of sport business. Empirical research concerns: the level of saturation of information and communication technology (ICT) in sport institutions and media coverage of organizational space in sport as the element of media technology development. The research has been conducted in the theory of organisational space (Cieśliński, 2016, 2017) and has been financed with the use of two research-implementation grants and implementation one under the operational program Program Operacyjny Polska Cyfrowa (POPC).